1986
DOI: 10.1073/pnas.83.16.5884
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive A X T pairs can adopt a left-handed DNA structure.

Abstract: The capacity of six sequences with different numbers and orientations of APT pairs flanked by alternating C'G pairs to adopt left-handed structures was evaluated in recombinant plasmids. A series of synthetic oligodeoxynucleotides were cloned into the BamHI site of pRW790, a small plasmid (=%2 kilobases) prepared especially for conformational studies of this type. Supercoil relaxation studies by twodimensional gel electrophoresis on topoisomers of each plasmid revealed the energetics and structures of the left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 44 publications
5
45
0
Order By: Relevance
“…[45][46][47] However, the functional impact of nucleotide repeats in terms of length on the promoter activity is still debated. Longer (GT)n repeats in the promoter of heme oxygenase-1 gene were associated with lower promoter activity.…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47] However, the functional impact of nucleotide repeats in terms of length on the promoter activity is still debated. Longer (GT)n repeats in the promoter of heme oxygenase-1 gene were associated with lower promoter activity.…”
Section: Discussionmentioning
confidence: 99%
“…The AÁT base pairs partially distort the overall Z-DNA structure by disrupting the hydration spine [16]. The ability of DNA duplexes to undergo the B-Z transition can be ordered as follows: (i) d(CG) repeat (which undergoes the transition most readily), (ii) d(TG/AC) repeat, (iii) d(GGGC) repeat, and (iv) d(TATA) repeat [19,20]. Recently, a structural study revealed that Za ADAR1 binds to the Z-conformation of both non-CG-repeat DNA duplexes and a d(CGCGCG) 2 duplex similarly, suggesting that Za ADAR1 recognizes Z-DNA through a common structural feature rather than by a specific sequence or structural alternations [21].…”
Section: Introductionmentioning
confidence: 99%
“…Because these characteristics correspond to established criteria for Z-DNA formation (55)(56)(57)(58)(59)(60)(61), it is probable that the APP element in the apoD promoter can form Z-DNA. Z-DNA conformations and APP sequences have been associated with both activation (62)(63)(64)(65) and repression (66 -70) of gene expression in mammalian cells.…”
Section: Mapping Of the Functional Elements Associated With The Growtmentioning
confidence: 99%